التكنولوجيا وأثرها على الصحة النفسية والجسمية لطلاب كلية التربية البدنية وعلوم الرياضة - همل أحمد عبدالله شعبان; السائح يوسف علي مفتاح; الصيد إبراهيم محمد يوسف (Al-Qurtas, 2026)
التكنولوجيا وأثرها على الصحة النفسية والجسمية لطلاب كلية التربية البدنية وعلوم الرياضة